Zero-sum views reduce support for redistribution across borders - Balietti, Anca; Mariño Fages, Diego (AWI discussion paper series, 2025)
This paper provides causal evidence on how zero-sum beliefs shape support for cross-border redistribution and economic openness. We implement a pre-registered two-by-two experiment with a broadly representative sample of 2,116 UK adults. The first treatment primes participants to adopt stronger or weaker zero-sum mindsets in general social and economic interactions, without reference to redistribution. Inducing a stronger zero-sum mindset significantly reduces donations to international anti-poverty organizations and modestly lowers stated support for international redistribution, migration, and trade. The second treatment provides information about respondents' position in the global income distribution. Learning one's relative global advantage fully offsets the negative effects of zero-sum priming. These results demonstrate that zero-sum beliefs causally reduce support for global redistribution and openness, but that making relative global affluence salient can neutralize this effect. The findings highlight a belief-based channel through which economic narratives shape public attitudes toward globalization, offering new insight into the appeal of rising nationalist and protectionist rhetoric in high-income countries.
Keywords: Graue Literatur